Epilepsy in childhood: findings from the National Child Development Study. Issue 6209 (26th January 1980) - Ross, E M; Peckham, C S; West, P B; Butler, N R
Abstract : By the age of 11 years 1043 children (6.7%) in an unselected national sample had a history of seizures or other episodes of loss of consciousness; 322 (20.8/1000) had a history of febrile convulsions without other epileptic problems. A clear-cut diagnosis of non-febrile epilepsy was established in 64 children (4.1/1000) by the age of 11 on the basis of confirmatory information supplied by family doctors and paediatricians. A further 39 (2.6/1000) were reported as having epilepsy but did not fulfil the study criteria. The progress of 59 of the 64 children with estabished epilepsy was reviewed again when they were aged 16. Of the 37 educated in normal schools eight (22%) had one or more seizures in their 16th year compared with 13 out of 22 (59%) who received special education. A possible cause for epilepsy was found in 17 of the 64 (27%) children, but for the majority there was no obvious reason.